Study Of The Parameter Interaction In A Closed_Loop Control Of A Process Intensification System - Ramli, Nor Hairie (Universiti Sains Malaysia, 2022)
In Process Intensification, innovative equipment and the integration of two or more units into a single piece of equipment are used. This has a significant influence on green technology, safer, cheaper, and superior chemical plants. Miniaturization and hybrid unit include the area of process intensification. Miniaturization entails the diminution of size, which expedites the process's reaction time. The rapid reaction renders the usual control mechanism incapable of controlling it. To meet this need, new control techniques together with a new actuator or sensor must be devised. In this work, the Direct Synthesis approach was utilised to develop the controller for an intensified system, taking into consideration all of the control loop's elements as well as several time delay approximations. Pade approximation of time delay yields PIDDD controller structure, while Taylor series expansion approximation of time delay yields PIDD controller structure. Variation of the time constant of the valve and sensor for each process time constant reveals the interaction between process state and process units for both controllers, which is explored. To enable a comparison of controller performance and parameter interaction with the PID controller form, the reduction order of the controller was also supplied. Performance is measured using Integral Absolute Error (IAE). For a fast process time constant